THE VIOLATION OF CONVERSATIONAL MAXIMS BY SALESPERSONS OF “REVLON” COSMETIC IN TWO DEPARTMENT STORES IN MALANG - KARTIKASARI, NIKEN WULAN (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: cooperative principle, violation of maxims, Revlon, salespersonsLanguage is a system to transfer and to inform something through communication. In the real life sometimes people do not obey the cooperative principles. The researcher conducts a study on the violation of conversational maxims by salespersons of “Revlon” cosmetic in two department stores in Malang. There are two problems in this study: (1) What maxims are violated by the salespersons of Revlon cosmetic while offering their products to customer? (2) What are the possible factors which cause the violation of certain maxims? This study answers the problems by using theory proposed by Paul Grice.This research used a qualitative method because the analysis conducted by the researcher was descriptive. The data are the utterances from the salespersons of Revlon cosmetic which contain violation of maxims.The results of this research show that there are 21 utterances containing violation of maxims produced by two salespersons in two different places which are Matahari Matos and Center Point MOG. In this research, maxim of quantity is often violated by those salespersons for 11 time; maxim of manner 8 time; maxim of quality 1 time; maxim of relation 1 time. The possible factors of violating a certain maxim in the salespersons utterances are: to explain more or stress something in order to make the hearers understand more; to hide the truth from the hearer and also to make the hearer believe in what the speakers say; to expect to get more attention from their customer by giving exaggerating statements about the products that they tried to offer to the customer; and to give information that they think is important.In conclusion, this study shows that violation can happen in the real life situation like in the conversation between the salespersons of Revlon cosmetic with the customers while offering the products. Finally after finishing this study, the researcher hopes that there will be more students in Faculty of Cultural Studies that do research in violation of maxims in their study.